ANALISIS PERBANDINGAN PENJUALAN KARGO SEBELUM DAN PADA SAAT PANDEMI COVID-19 DI PT. GARUDA INDONESIA (PERSERO) TBK CABANG. TANJUNG KARANG LAMPUNG - Azhar, Faizal; Damayanti, Damayanti; Damayanti, Hani (Jurnal Kompetitif Bisnis, 2022)
This study aims to determine the comparison of cargo sales before and during the covid-19 pandemic at PT. Garuda Indonesia (Persero) Tbk. Branch. Tanjung Karang, Lampung. This study uses a quantitative approach with the type of research associative through literature study, observation and interviews. The data used is the growth of cargo sales for 48 months, from January 2018 to December 2021. The data processing in this study is the Parametric Paired Sample T-Test and the Wilcoxon Non Parametric Test, with the help of SPSS version 28.0. The results of this study indicate that there is no significant difference between cargo sales before and during the covid-19 pandemic at PT. Garuda Indonesia (Persero) Tbk. Branch. Tanjung Karang, Lampung. The Paired Sample T-Test and the Wilcoxon Rank Test, respectively, showed numbers 0.686 and 0.721 or greater than the 0.05 significance level. The average difference in cargo sales growth was only 18.362%, this was due to changes in management policies such as reducing the number of aircraft, changing types of aircraft with smaller capacities and reducing flight schedules which made the company’s cargo sales not optimal during the covid-19 pandemic.